Filaria specific antibody response profiling in plasma from anti-retroviral naïve Loa loa microfilaraemic HIV-1 infected people - Ghislain Donald Njambe Priso; Abel Lissom; Loveline N. NGU; Nadesh N. Nji; Jules Colince Tchadji; Thibau Flaurant Tchouangueu; Georgia E. Ambada; Carole Stéphanie Sake Ngane; Brigitte Laure Dafeu; Larissa Djukouo; Inès Nyebe; Suzanne Magagoum; et al. (BMC Infectious Diseases, 2018)
Abstract Background In West and Central Africa areas of endemic Loa loa infections overlap with regions of high prevalence of human immunodeficiency virus type 1 (HIV-1) infections. Because individuals in this region are exposed to filarial parasites from birth, most HIV-1 infected individuals invariably also have a history of filarial parasite infection. Since HIV-1 infection both depletes immune system and maintains it in perpetual inflammation, this can hamper Loa loa filarial parasite mediated immune modulation, leading to enhanced loaisis. Methods In this study we have assessed in plasma from asymptomatic anti-retroviral (ARV) naïve Loa loa microfilaraemic HIV-1 infected people the filarial antibody responses specific to a filariasis composite antigen consisting of Wbgp29-BmR1-BmM14-WbSXP. The antibody responses specific to the filariasis composite antigen was determined by enzyme linked immunosorbent assay (ELISA) in plasma from ARV naïve Loa loa microfilaraemic HIV-1 infected participants. In addition the filarial antigen specific IgG antibody subclass profiles were also determined for both HIV-1 positive and negative people. Results Both Loa loa microfilaraemic HIV-1 positive and negative individuals showed significantly higher plasma levels of IgG1 (P < 0.0001), IgG2 (P < 0.0001) and IgM (P < 0.0001) relative to amicrofilaraemic participants. A significant increase in IgE (P < 0.0001) was observed exclusively in Loa loa microfilaraemic HIV-1 infected people. In contrast there was a significant reduction in the level of IgG4 (p < 0.0001) and IgG3 (P < 0.0001) in Loa loa microfilaraemic HIV-1 infected individuals. Conclusions Loa loa microfilaraemia in ARV naïve HIV-1 infected people through differential reduction of plasma levels of filarial antigen specific IgG3, IgG4 and a significant increase in plasma levels of filarial antigen specific IgE could diminish Loa loa mediated immune-regulation. This in effect can result to increase loaisis mediated immunopathology in antiretroviral naive HIV-1 infected people.